Relationship between perfectionism and attitudes toward doping in young athletes: the mediating role of autonomous and controlled motivation - Kun Wang; Lei Xu; Jimeng Zhang; Dong Wang; Kaihong Sun (BMC, 2020)
Abstract Background Recent studies suggest that autonomous and controlled motivation may mediate the relationship between perfectionism and attitudes toward doping. The purpose of this study was to investigate the association among perfectionistic strivings, perfectionistic concerns, autonomous motivation, controlled motivation, and attitudes toward doping in young athletes. The potential mediating role of autonomous and controlled motivation was examined. Methods Two hundred and forty-three Chinese athletes were surveyed using questionnaires. Structural equation modeling (SEM) was conducted to evaluate the potential mediating role of autonomous and controlled motivation between perfectionism and attitudes toward doping. Results The results showed that perfectionistic strivings was negatively associated with attitudes toward doping, whereas perfectionistic concerns positively predicted attitudes toward doping. Autonomous motivation was negatively associated with attitudes toward doping, whereas controlled motivation positively predicted attitudes toward doping. The mediation analyses showed that the relationship between perfectionistic strivings and attitudes toward doping was partially mediated by autonomous motivation. The relationship between perfectionistic concerns and attitudes toward doping was partially mediated by controlled motivation. Conclusions The findings suggested that fostering perfectionistic strivings and autonomous motivation and reducing perfectionistic concerns and controlled motivation may be considered for inclusion in athletes' anti-doping education.